Analysis of the Catering Sector’s Adjustment Plan following the COVID-19 Pandemic - Han Yike (SHS Web of Conferences)
The conventional catering business was severely impacted by the COVID-19 pandemic, but this also markedly expedited the industry’s shift to digitalisation. According to the report, the catering industry modified its business plan in response to the COVID-19 pandemic, taking into account the extensive effects on the sector. Following the epidemic’s conclusion, the catering business has experienced a rapid digital change due to the persistent price increases. Contactless delivery, online ordering, and intelligent management have emerged as the key themes. Additionally, catering businesses need to improve client trust and focus on food safety and hygiene. At the same time, businesses are now competing primarily on enhancing customer experience and service quality. In conclusion, this research recommends that catering companies should be able to adapt their business plans in order to handle future emergencies. By making these changes, the catering sector may both recover from the pandemic’s losses and achieve sustained growth in the years following.